Framing the Floods: Temporal Shifts and Ecological Silences in Indonesian Media - Husni, Mochamad (Communica : Journal of Communication, 2025)
Indonesia's increasing flood frequency and severity underscore the urgent need for comprehensive disaster reporting that highlights both natural and anthropogenic causes. This study investigates temporal changes in the media framing of flood disasters between 2020 and 2025, with a focus on ecological narratives in Indonesian online news outlets. Using Entman’s four-frame model problem definition, causal attribution, moral evaluation, and remedy recommendation this research analyzed 60 articles from five national media platforms. The articles, covering events in Jakarta, Kalimantan, Jabodetabek, and Pekalongan, were examined using NVivo-assisted coding and critical discourse analysis supported by ecolinguistic perspectives. Results show a persistent reliance on natural disaster framing in both 2020 and 2025, with technical and infrastructural narratives increasingly dominant in recent years. While there is a gradual integration of scientific and policy-relevant vocabulary such as “climate adaptation” and “urban resilience” ecological degradation remains underreported. Comparisons between years reveal an incremental shift toward accountability framing, yet ecological drivers like deforestation or land-use mismanagement continue to receive minimal attention. Furthermore, reliance on official sources and episodic coverage patterns limit public engagement with systemic environmental issues. The discussion highlights structural constraints including corporate influence, low media literacy, regulatory barriers, and editorial dependence on government narratives. Lessons from Global South countries illustrate how integrating grassroots voices and improving journalist training can strengthen environmental reporting. The study concludes by advocating for institutional reforms, enhanced ecological literacy, and the empowerment of community journalism as steps toward more transformative media practices.